Sentential Styles in Students' Writing - Israel, Peace Chinwendu (NIU Journal of Humanities, 2022)
This study explored sentential styles undergraduates employ in their writing and their effectiveness in communication. The purpose of this exploration is to ascertain the degree to which they display knowledge of various sentential styles and their effectiveness in achieving clarity, precision and grace. Lawal (2012) explication of style as choice from variant forms and style as idiosyncratic and constant forms was employed in the analysis.  An essay topic written by selected second year students of the University of Education, Winneba formed the data. The result revealed significant difference in the sentential styles used by the students in their writing. The mixed sentence style was dominant, followed by loose sentence style. The next in rank was periodic sentence, while parallel and balanced sentence styles were absent. This clearly suggests that there is monotony in their writing style and monotonous writing is ineffective writing style. The paper concluded by recommending possible solutions to effective and elegant writing for effective communication and enhanced performance in English. Keywords: Writing, Sentential style, Styles as choice, Effective Communication